The Impact of Teacher-Student Relationships on Teachers’ Job Satisfaction in a Vocational College in Hubei, China - LUO, RUI (Pacific International Journal, 2024)
The significance of teacher-student relationships in shaping the learning experience and teacher job satisfaction is increasingly recognized. This paper studies this phenomenon within the unique context of Xianning Vocational Technical College in Hubei, China. The college’s cultural backdrop, characterized by reverence for authority and evolving pedagogical approaches, adds complexity to the dynamics of teacher-student interactions. A qualitative research design involving 50 participants, including teachers and students, sheds light on this intricate relationship. Key findings reveal that positive teacher-student interactions significantly influence teacher job satisfaction. Teachers who establish rapport with students and enjoy teaching autonomy report higher job satisfaction. Professional development, recognition, and support systems also play pivotal roles. Comparisons with other educational settings highlight vocational colleges’ distinctive characteristics, such as the emphasis on practical skills and smaller class sizes, fostering closer relationships and enhancing job satisfaction. Implications for educational practices underscore the importance of promoting positive teacher-student relationships, balancing teaching autonomy, and recognizing and supporting educators. Recommendations include mentoring programs, student feedback mechanisms, and inclusive classroom activities. Additionally, policy considerations advocate for supporting vocational colleges to create a conducive teaching and learning environment.